2022
DOI: 10.3390/healthcare10040664
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Empowerment and Organizational Commitment from Nurse’s Perspective in the Ministry of Health Hospitals

Abstract: (1) Background: The nurse structure is the largest proportion of the healthcare team in hospitals and Primary Healthcare Centers (PHCs). Empowerment is considered a vital component in strategic planning implementation and plays an important role in enhancing job commitment, motivation and employee satisfaction. (2) Aim: The aim of this study is to examine the relationship between the empowerment and organizational commitment from a nurse’s perspective in the MOH in Makkah city in Saudi Arabia. (3) Methods: A d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This leads to a broader concept, rather than merely performing the activities in the work process, because the workforce needs to be empowered. Some studies addressing nursing workers in hospitals in Saudi Arabia [ 58 ], Egypt [ 59 ], and Greece [ 60 ] showed that empowering workers favors positive bonds with the health organization, affective commitment, job satisfaction, and job involvement.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to a broader concept, rather than merely performing the activities in the work process, because the workforce needs to be empowered. Some studies addressing nursing workers in hospitals in Saudi Arabia [ 58 ], Egypt [ 59 ], and Greece [ 60 ] showed that empowering workers favors positive bonds with the health organization, affective commitment, job satisfaction, and job involvement.…”
Section: Discussionmentioning
confidence: 99%
“…NPs with supportive working environments might fully practice their professional role which promotes organizational commitment. Moreover, recent studies had showed that organizational support is a vital factor in enhancing work commitment [58,59]. Terefore, healthcare organizations are suggested to modify policies to balance the practice rights of NPs and physicians in the collaborative practice model, which might strengthen the organizational commitment and improve job satisfaction of NPs.…”
Section: Variables Afecting Job Satisfactionmentioning
confidence: 99%